A laity who know their religion: the theological education of the laity in John Henry Newman - Jumbam, Jerry (Collection "Culture and faith", 2018)
An accomplished overview of Christianity's original idea of the laity and their theological formation, in the truest spirit of John Henry Newman. Gerald Jumbam Nyuykongmo's pioneering contributions to the role of the laity in the Church is hugely impressive and his emphasis on theological education of the laity makes the book soar. The work is a revelatory entry into the Post-Vatican spirit of understanding between clergy and laity and therefore on how the laity can take their place, not at the peripheries, but rather at the very core of Church life